Correction: Tumor acidity-responsive carrier-free nanodrugs based on targeting activation via ICG-templated assembly for NIR-II imaging-guided photothermal-chemotherapy. (7th January 2021) - Xue, Kaihang; Wei, Feng; Lin, Jinyan; Tian, Haina; Zhu, Fukai; Li, Yang; Hou, Zhenqing
Abstract : Correction for 'Tumor acidity-responsive carrier-free nanodrugs based on targeting activation via ICG-templated assembly for NIR-II imaging-guided photothermal-chemotherapy' by Kaihang Xue et al., Biomater. Sci., 2021, DOI: ; 10.1039/D0BM01864C .